An investigation on temperature sensitivity of conductive carbon coated fiber Bragg grating - M. K., Mohd Yusof; Jamaluddin, M. N. H.; Muhammad, Farah Diana; Lim, K. S.; Ahmad, H.; Zulkifli, M. Z. (Elsevier, 2021)
We propose a conductive carbon coated fiber Bragg grating (FBG) temperature sensor for enhancing temperature sensitivity. The temperature sensitivity of the proposed sensor is effectively enhanced by approximately 4 times higher than those of the bare-type FBG sensors due to thermal expansion and physical stress possessed by the conductive carbon coating, with the operating temperature ranging from 40 °C to 260 °C. The proposed sensor is much more convenient to fabricate compared to other similarly coated FBG sensors, giving a leap advantage of easy reformation of the coating to fit various housings. This proposed sensor is significantly ideal for various applications such as optoelectronic circuit and waveguide temperature measurement.